EARLY WARNING SCORES IN ONCO-HEMATOLOGICAL PATIENTS: AN INTEGRATIVE REVIEW OF THEIR APPLICABILITY IN THE AMAZONIAN CONTEXT - Alves, Chesman da Silva; de Vasconcelos, Tayane Cristine Verçosa; Tarragô, Andrea Monteiro; Cardoso, Evilázio Cunha; Ferreira, Cristina Motta (ARACÊ, 2025)
The increasing incidence of hematologic malignancies highlights the need to expand the use of Early Warning Scores (EWS) in this clinical context. However, the application of these tools in onco-hematological patients remains underexplored. This study aims to summarize the scientific evidence regarding the effectiveness of Early Warning Scores (EWS) in the early detection of clinical deterioration in onco-hematological patients and their applicability in the Amazonian context. This integrative literature review was conducted between August and November 2024, utilizing the following databases: Scientific Electronic Library Online (SciELO), Latin American and Caribbean Health Sciences Literature (LILACS), PUBMED, MEDLINE, Fundación Index Bibliographic Database (CUIDEN), Nursing Database (BDENF), accessed via the Virtual Health Library (VHL) portal, and Google Scholar. A total of 15 studies addressing the use of early warning scores in onco-hematological patients were identified, with emphasis on MEWS (Early Warning Score), NEWS (National Early Warning), PEWS (Pediatric Early Warning Score), and Qsofa (Xx), among others. All studies were conducted in an international context, revealing a research gap in Brazil and other vulnerable regions, such as the Amazon.